2018
DOI: 10.1080/14786419.2018.1434633
|View full text |Cite
|
Sign up to set email alerts
|

Saponin-rich fraction from Agave sisalana: effect against malignant astrocytic cells and its chemical characterisation by ESI-MS/MS

Abstract: Astrocytic tumour cells derived from human (GL-15) and rat (C6) gliomas, as well as non-tumoural astrocytic cells, were exposed to the saponin-rich fraction (SF) from Agave sisalana waste and the cytotoxic effects were evaluated. Cytotoxicity assays revealed a reduction of cell viability that was more intensive in glioma than in non-tumoural cells. The SF induced morphological changes in C6 cells. They were characterised by cytoplasmic vacuole formation associated with increase in the formation of acidic lysos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The smaller size of agave expansin genes might be due to tissue-specific expression or the limitation of RNA-Seq in our study. Although a series of saponin-related [ 25 ] and fructan-related [ 26 ] research studies have been reported, few reports were related to fiber development. Therefore, these expansin genes we identified can serve as guidance for further studies on agave fiber development.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller size of agave expansin genes might be due to tissue-specific expression or the limitation of RNA-Seq in our study. Although a series of saponin-related [ 25 ] and fructan-related [ 26 ] research studies have been reported, few reports were related to fiber development. Therefore, these expansin genes we identified can serve as guidance for further studies on agave fiber development.…”
Section: Discussionmentioning
confidence: 99%